"Teaching and educating preschool children with intellectual disabilities" - Nematova Shirinoy Nizomiddinovna (Zien Journals, 2022)
This article describes the content, purpose, and issues of social adaptation of correctional work with young preschool children with intellectual disabilities. The results of correctional educational work are determined by the interaction of adults with the child, the nature of children's interaction. Based on the results of a comprehensive diagnostic examination, the child is subjected to uniform requirements in the family and in the preschool institution
Keywords: education; pedagogy; personal development; diagnostic examination